The Physicochemical and Sensory Properties of Whey-Fed Pork Loin after Salting, Dry Aging, and Sous Vide Cooking - Fengqi Yang; Chi-Ho Lee; Min-Young Jeon; Won-Young Cho; Han Geuk Seo (Journal of Chemistry)
This study was conducted to evaluate the physicochemical properties of whey-fed pork loin subjected to salting, dry aging, and sous vide cooking. We compared raw and treated pork loin from pigs fed a basal diet (control) and those fed a diet supplemented with whey powder. Treated pork was salted, dry aged for 0–30 d, and then cooked using sous vide. The crude fat, total lipid, and cholesterol content and shear force of raw whey powder-fed pork loin were significantly lower than those of the control, while the crude protein content was higher. Cooking loss, hardness, and gumminess were found to decrease with the aging period in sous vide-treated pork. Dietary supplementation with whey had positive effects on pork color stability, texture, and sensory evaluation, and it significantly inhibited the growth of bacteria. The results suggest that supplementing the diet of pigs with whey powder can enhance meat quality, especially when combined with salting, dry aging, and sous vide cooking.